[Construction of the Interior of Kennedy Library] - P. K. Phillips::::::photographer::: (1978)
Construction of the interior of Kennedy Library, facing the atrium. The main staircase and multiple floors of the library are pictured. Also in frame are construction materials and the crane used for completing the building.